Effects of pH and Electrolytes on Castor Oil Emulsions with Various Stabilisers Using Khaya senegalensis Gum as an Emulsifier - Deryl Nii Okantey Kuevi; Noble Kuntworbe; Enoch Ayertey (Advances in Pharmacological and Pharmaceutical Sciences)
Dispersed systems such as emulsions are easily destabilised during processing and storage since they are thermodynamically unstable systems. It is for this reason emulsifiers/stabilisers are frequently employed in pharmaceutical emulsion formulations to increase their short- and long-term kinetic stability. This current study seeks to investigate the potential emulsifying property of gums obtained from Khaya senegalensis (family: Meliaceae) trees. Gums were collected, authenticated, oven-dried, milled, filtered, and purified using 96% ethanol. The microbial quality of the gum was assessed following the BP (2013) specifications. The purified gum was free from some selected pathogenic microorganisms, rendering the gum safe for consumption. The emulsifying property was investigated by formulating emulsions using castor oil and employing the dry gum method. The ratios of oil-to-water-to-gum for the formulation of a stable emulsion were determined. The stability of the emulsion was evaluated, and an effort was made to improve the stability by incorporating Tween 80, hydroxypropyl methylcellulose, and xanthan gum. From the results, it can be inferred that Tween 80 (0.5%) was able to stabilise the emulsion. Addition of xanthan gum worsened the creaming. The effects of pH (4.0, 5.5, 7.2, 9.0, and 11.0) and electrolytes (0.1 M of NaCl, KCl, and CaCl2) on the physical stability of oil-in-water emulsions were studied during 12 weeks of storage. Percentage creaming volume and whether there was phase inversion were the criteria used as the evaluation parameter. From the percentage creaming volume data, emulsions formulated with both gums showed the lowest creaming volumes at pH of 7.2, followed by the acidic regions (pH 4.0, 5.5), with the basic regions (pH 9.0, 11.0) recording the highest creaming volumes. The effects of the various electrolytes at a constant concentration of 0.1 M on the o/w emulsions were found in this order NaCl < KCl < CaCl2. This study proves that Khaya senegalensis gum can successfully be employed as an emulsifying agent in pharmaceutical formulations.